Polyarthritis and angioimmunoblastic lymphadenopathy. - McHugh, N J (1987)
Angioimmunoblastic lymphadenopathy (AILD) is a lymphoproliferative disorder with well established clinical and histological features, one of the clinical manifestations being a peripheral polyarthritis. A case of AILD with a symmetrical non-erosive peripheral polyarthritis is described, including the findings in the synovial fluid and histology of the synovium. There was a marked reduction in the number of peripheral blood T lymphocytes bearing the CDT8 phenotype in both the peripheral blood and synovial fluid. The arthritis was difficult to control, requiring large doses of corticosteroids, which produced significant side effects. Levamisole 150 mg, one day each week, was effective in controlling the arthritis and returning the numbers of CDT8 lymphocytes to normal. The aetiology of AILD is unknown, though a defect in T cell regulation, in particular T cell suppression, with a secondary B cell proliferation has been postulated. The demonstration of reduced numbers of lymphocytes bearing the CDT8 phenotype in this patient supports that theory.